Investigation of Time Series of Original Values of Currency Rates Measured on Small Time Frames on FOREX Using Methods of Chaos Theory - Dabi-Prash, O.; Kirichenko, L. (ХНУРЭ, 2009)
Lately, the linear paradigm with its idea of normal distribution of profits has been replaced with the nonlinear approach and Chaos Theory which gives the explanation of the complex behavior of financial markets. It has been discovered that time series of profits measured on long time frames on currency and stock markets (time series of monthly prices etc.) are chaotic. This paper is concentrated on investigation of time series of original values of currency rates measured on short time frames on FOREX (hourly, 4-hourly, daily prices) using methods of Chaos Theory (Time-delay reconstruction method, Grassberger-Procaccia method, estimation of the Lyapunov exponent) in order to define if such time series are chaotic as well.
Keywords: small (short) time frames; predictability of financial time series; memory in financial; Chaos theory; FOREX